2012
DOI: 10.1007/s00432-012-1153-y
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-rP1 induces p21 expression through a p53-independent pathway, leading to cellular senescence of MCF-7 breast cancer cells

Abstract: Results from this study suggest that cellular senescence induced by IGFBP-rP1 is mediated at least in part by p21 enhanced expression, which regulated through the p53-independent pathway. IGFBP-rP1 might be one of the key molecules that trigger cellular senescence in breast cancer. Restoration of IGFBP-rP1 function might have therapeutic significance in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
1
36
0
1
Order By: Relevance
“…Importantly, both TIMP-2 and IGFBP7 appear to be able to signal in autocrine and paracrine fashions [24,27-30] thus spreading the 'alarm' from the site of injury. In terms of timing, this signal could be ideal as it may be early enough that treatment can still alter the outcome - further study will be required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both TIMP-2 and IGFBP7 appear to be able to signal in autocrine and paracrine fashions [24,27-30] thus spreading the 'alarm' from the site of injury. In terms of timing, this signal could be ideal as it may be early enough that treatment can still alter the outcome - further study will be required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is grounded in data from in vitro studies of colon and breast cancer cell lines, which have shown the capacity of IGFBP7 to induce G 1 cell cycle arrest and senescence, as well as a study of melanocyte and melanoma cell lines, which has shown that IGFBP7 regulates proliferation and senescence (80,81). These studies have reported that the effects of IGFBP7 are mediated by increased expression of p21 and p53 as well as inhibition of mitogen-activated protein kinase signaling (80)(81)(82). However, it is also plausible that elevated IGFBP7 could have a deleterious effect on the injured kidney, because IGFBP7 is an IGF-1 receptor antagonist (83).…”
Section: Igfbp7mentioning
confidence: 99%
“…19 Several IGF-independent effects, such as tumor suppression in melanoma and colon cancer, and induction of cell senescence in breast cancer lines, are also ascribed to IGFBP7. 2021 …”
Section: Biological Functions Of Timp-2 and Igfbp7mentioning
confidence: 99%